Implementation and feasibility of green hydrogen in Colombian kitchens: an analysis of innovation and sustainability - Jhon Vidal-Durango; Rubén Baena-Navarro; Kevin Therán-Nieto (Institute of Advanced Engineering and Science, 2024)
This study explores the potential of green hydrogen as a sustainable energy solution in domestic cooking, focusing on Colombia. It employs a systematic literature review following the PRISMA framework, analyzing articles published between 2018 and 2023 to assess the feasibility and challenges of implementing green hydrogen in the culinary sector. The research emphasizes the projected growth in the demand for clean hydrogen, particularly in the industrial sector by 2030 and in new applications by 2050, with an estimated increase from less than 1% currently to about 30% of the total hydrogen demand. It is anticipated that green hydrogen production will dominate the global supply mix by 2050, reflecting a share of between 50% and 65% in various scenarios. The study concludes that while green hydrogen holds great potential for transforming Colombia's energy matrix towards a cleaner, more sustainable future, it faces significant regulatory and technical challenges that require concerted, collaborative action, aligning with the sustainable development goals.